Analisis Kemampuan Numerasi Peserta Didik Kelas 1 Madrasah Ibtidaiyah Berdasarkan Level Kognitif - Zulfa Zachri Wahyudi; Nurdiana Siregar; Rora Rizky Wandini (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to identify the numeracy ability of grade I students of Madrasah Ibtidaiyah Based on Cognitive Level. The research method used is quantitative with a descriptive approach. The population used by all students of MIN 4 Medan. Sampling from the population used the Issac Michael technique which obtained a result of 249 from the entire population. Furthermore, samples were taken using cluster sampling which was specifically for classes I, A and I B, a total of 56. The test instrument is in the form of an objective description of the "filling" and the results are in the form of scores. The data analysis in this study is a descriptive quantitative data analysis. The results showed the numeracy ability of students in class I MIN 4 Medan, namely: 1) the level of remembering for the "high" category was 37 students or 75.51%; for the "medium" category: there are 4 students or 8.16%; and the "low" category there are 8 students or 16.32%. 2) the level of understanding for the "high" category was 28 students or 57.41%; the "medium" category has 16 students or 32.65%; and the "low" category there are 5 students or 10.20%. 3) the application rate for the "high" category was 18 students or 36.73%; the "medium" category has 29 students or 59.18%; and the "low" category has 2 students or 4.08%. The implication in this study is to increase the practice of contextual questions and carry out game-based learning.